Integrasi Eco-Brick dan Teknologi Digital dalam Pengelolaan Sampah Perkotaan: Praktik Komunitas di Banjarmasin - Budiman, Mochammad Arif; Pebriadi, Muhammad Syahid; Mairijani, Mairijani (Universitas Pahlawan Tuanku Tambusai, 2026)
Banjarmasin City faces serious challenges in urban waste management due to high waste generation, limited facilities, and low public awareness of waste segregation. This community service program aims to integrate eco-brick practices and digital technology in community-based waste management in RT 19, Alalak Tengah Village, Banjarmasin. The methods applied include waste segregation education and training, eco-brick production, provision of waste processing facilities, Clean and Healthy Living Behavior (PHBS) campaigns, and digital mapping of waste production areas using the CLEANMAP-BJM application. The results indicate a significant increase in community understanding of waste management (92.7%), a reduction in waste disposed of at temporary collection points, and the creation of value-added products such as eco-brick-based sofas. The integration of ecological approaches and digital technology effectively enhances community participation and supports more sustainable urban waste management.